1998
DOI: 10.2116/analsci.14.199
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Charge Transfer near a Hydrophobic Surface. 2,6-p-Toluidinonaphthalene Sulfonate in a Reverse Micelle

Abstract: The behavior of an organic molecule at an interface between two bulk media is often significantly different from that in either of the bulk medium. Since the polarity and viscosity at the interface are often very much different from those of the bulk media, the structure, dynamics and reactivity of an organic or biomolecule at an interface differ markedly from those in the bulk. Interestingly most natural and biological processes occur at such interfaces or confined systems, such as proteins, biomembranes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…7,[13][14][15][16][17][18][19][20][21] As an example, Cho et al reported that ANS in reverse AOT micelles exhibited a double exponential decay: short component=0.3 -0.6 ns and long component=2.6 -5.1 ns at w 0 =4 -33.…”
Section: Fluorescence Dynamics Of Ans In Reverse Aot Micelles and Itsmentioning
confidence: 99%
See 3 more Smart Citations
“…7,[13][14][15][16][17][18][19][20][21] As an example, Cho et al reported that ANS in reverse AOT micelles exhibited a double exponential decay: short component=0.3 -0.6 ns and long component=2.6 -5.1 ns at w 0 =4 -33.…”
Section: Fluorescence Dynamics Of Ans In Reverse Aot Micelles and Itsmentioning
confidence: 99%
“…So far, a number of spectroscopic studies have been reported on reverse AOT micelles. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] However, detailed discussion based on k nr has been rarely explored. The present study showed clearly that detailed analysis of the photophysical parameters was essential to discuss fluorescence characteristics of a probe molecule in reverse micelle systems.…”
Section: Energy Gap Dependence Of the Non-radiative Rate Constant Of Ansmentioning
confidence: 99%
See 2 more Smart Citations
“…This photophysical scheme, however, has been questioned, mainly in supramolecular assemblies. 2,[17][18][19][20][21] In another approach, the p ! p* emission band of this type of fluorescent probe is believed to consist of different bands, each of which is attributable to the p !…”
Section: Introductionmentioning
confidence: 99%